Identification of the gene encoding the DNA (cytosine-5) methyltransferase of lymphocystis disease virus - Tidona, Christian; Schnitzler, Paul; Kehm, Roland; Darai, Gholamreza (Virus genes, 1996)
The gene encoding the DNA (cytosine-5) methyltransferase (m5C-MTase) of lymphocystis disease virus (flounder isolate, LCDV-1) has been identified by polymerase chain reaction (PCR) using oligonucleotide primers synthesized corresponding to different regions of the m5C-MTase gene of frog virus 3 (FV3). A DNA fragment of 487 bp was amplified using oligonucleotide primers L3 and R4 which correspond to the nucleotide positions 87 to 109 and 530 to 550 of the m5C-MTase gene of FV3, respectively. The DNA nucleotide sequence of the PCR product was determined by direct cycle sequencing. The alignment of the deduced amino acid sequence derived from the PCR product and the m5C-MTase protein of FV3 revealed a homology of 55.4% identity and 29.1% similarity. The amino acid sequence which was found to be significantly homologous to the amino acid sequence deduced from the nucleotide sequence of the PCR product was located at the amino acid position 37 to 175 of the m5C-MTase of FV3 indicating the specificity of the amplified PCR product. The DNA nucleotide sequence of the LCDV-1 genome corresponding to the 5′ and 3′ termini of the m5C-MTase gene was determined by primer walking. The locus of the m5C-MTase gene of LCDV-1 was identified within the EcoRI DNA fragment G of LCDV-1 (7.9 kbp; 0.947 to 0.034 map units). The m5C-MTase gene of LCDV-1 comprises 684 nucleotides coding for a putative protein of 228 amino acid residues. A high degree of amino acid sequence homology (53.3% identity and 25.8% similarity) was detected between the m5C-MTases of LCDV-1 and FV3.
Gesehen am 29.08.2024